2012
DOI: 10.5923/j.ijaf.20120202.08
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Climate Change Impacts on Agriculture and Food Security in Nigeria

Abstract: 8%)) went to agricultural sector. The actual spending was 681 billion Naira per year with 11.4 billion Naira for agriculture. Over 25 years, there were low and dramatic walloping of public spending in agriculture relative to large size and importance of agricultural sector in the economy. There is a continuous rise in output from 1987 to 2000 before it dropped in 2001. Land degradation, desert encroachment, drying up of surface waters, coastal inundations, and shift in cultivated crops over time affected the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 6 publications
3
8
0
Order By: Relevance
“…Increase in temperature especially in the semi arid region Ladan 181 has resulted in the less farm work as farmers and other farm workers get tired easily due to dehydration and constant sweating. This was supported by Bello et al (2012) who indicate that sudden increase in air temperature in Nigeria was observed as from the early 1970s until 2005 which is linked to the effect of climate change and its associated global warming which was previously reported by several studies. The mean air temperature from 1901-1970 was 26.3 0 C and increases to 27.8 0 C from 1971-2005(Bello et al, 2012.…”
Section: Increase In Temperaturesupporting
confidence: 69%
See 1 more Smart Citation
“…Increase in temperature especially in the semi arid region Ladan 181 has resulted in the less farm work as farmers and other farm workers get tired easily due to dehydration and constant sweating. This was supported by Bello et al (2012) who indicate that sudden increase in air temperature in Nigeria was observed as from the early 1970s until 2005 which is linked to the effect of climate change and its associated global warming which was previously reported by several studies. The mean air temperature from 1901-1970 was 26.3 0 C and increases to 27.8 0 C from 1971-2005(Bello et al, 2012.…”
Section: Increase In Temperaturesupporting
confidence: 69%
“…This was supported by Bello et al (2012) who indicate that sudden increase in air temperature in Nigeria was observed as from the early 1970s until 2005 which is linked to the effect of climate change and its associated global warming which was previously reported by several studies. The mean air temperature from 1901-1970 was 26.3 0 C and increases to 27.8 0 C from 1971-2005(Bello et al, 2012. Also farmers continue to complain that agricultural produce has been very poor these days as they are facing declining crop yields due to weather fluctuations and other environmental threats.…”
Section: Increase In Temperaturesupporting
confidence: 69%
“…Most of the studies on climate change in Nigeria are concerned with effects, impacts and adaptions [21]. Among such studies in Africa and Nigeria are: evidence of climate change impacts on agriculture and food security in Nigeria [22], awareness and adaptation to climate change among yam-based farmers in rural Oyo state, Nigeria [23] and agricultural vulnerability to climate change in eight selected rural settlements in Sokoto State, Nigeria [24].…”
Section: Statement Of Research Problemmentioning
confidence: 99%
“…Way before crude oil was discovered in commercial quantity in Nigeria, agriculture was the major trade and source of livelihood and economic growth. Agriculture is still rich in the country's growth and plays a vital role in economic growth so it has to be protected [7].…”
Section: Introductionmentioning
confidence: 99%